2011
DOI: 10.1016/j.jcmg.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of Carotid Plaque Composition During Lipid-Lowering Therapy

Abstract: OBJECTIVES The purpose of this study was to test the lipid depletion hypothesis and to establish the time course of change in carotid plaque morphology and composition during lipid therapy using high-resolution magnetic resonance imaging (MRI). BACKGROUND Lipid therapy is thought to improve plaque stability and reduce cardiovascular events by targeting the plaque rupture risk features such as large lipid core, thin fibrous cap, and high level of inflammatory infiltrates. However, the plaque stabilizing proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(93 citation statements)
references
References 33 publications
(32 reference statements)
5
86
1
1
Order By: Relevance
“…93 Another trial used MR plaque imaging to demonstrate that intensive lipid therapy with atorvastatin resulted in significant reductions in the carotid plaque LRNC volume. 128 Serial MRI studies have also demonstrated that high-dose rosuvastatin is associated with marked (60%) reduction in LRNC volume. 112 MR plaque imaging has also been used to identify surgical candidates.…”
Section: Medical and Surgical Therapymentioning
confidence: 98%
“…93 Another trial used MR plaque imaging to demonstrate that intensive lipid therapy with atorvastatin resulted in significant reductions in the carotid plaque LRNC volume. 128 Serial MRI studies have also demonstrated that high-dose rosuvastatin is associated with marked (60%) reduction in LRNC volume. 112 MR plaque imaging has also been used to identify surgical candidates.…”
Section: Medical and Surgical Therapymentioning
confidence: 98%
“…The lipid depletion theory suggests that plaque stability is improved and cardiovascular events are reduced with medical treatment such as statin therapy to deplete lipids and decrease the LRNC size. 37 Multicontrast MRI of the carotid arteries has been validated with histology and shown to identify and quantify various carotid plaque components including the LRNC, FC, and IPH (Fig. 2).…”
Section: Lipid-rich Necrotic Core With Thin Fcmentioning
confidence: 99%
“…After 3 years of lipid therapy, these 33 subjects had a significant reduction in plaque lipid content. 37 For the first time, an understanding of the time course was provided, with statistically significant plaque lipid depletion observed after 1 year of treatment and continuing into the 2nd year. The LRNC size reduction preceded the plaque regression, consistent with the lipid depletion therapy.…”
mentioning
confidence: 99%
“…Alternatively, vitamin D may have an effect on the lipid-rich necrotic core where microhemorrhages occur. Most interesting, while statins have been shown to decrease the carotid lipid-rich necrotic core 47 and decrease plaque inflammation, 48 This finding suggests an interaction between statins and vitamin D, and optimizing both may be important in treating patients with carotid IPH. One limitation of our study is its cross-sectional nature, making it difficult to determine causation between low vitamin D levels and carotid IPH.…”
Section: Discussionmentioning
confidence: 99%